UP-TO-DATE APPROACHES IN TREATMENT OF HYDATID DISEASE OF THE LIVER IN CHILDHOOD - S. V. Minaev; I. N. Gerasimenko; N. I. Bykov; S. V. Timofeev (Вестник хирургии имени И.И. Грекова)
Sixty children (age 3–15 years) with hydatid disease of the liver were treated. The patients were divided into 2 equal groups (control and main groups).The hydatid disease of the liver was revealed in 22 (33,6%) patients, combined hydatid disease of the liver and lung were noted in 38 (66,4%) patients. The «capitonnage» of the residual cavity was applied in the control group and omentoplasty — in the main group. Chemotherapy with Nemazol (dose 10–15 mg/kg/day) was carried out. In order to reduce the negative influence of Nemazol on patients and to accelerate reparation processes of liver parenchyma Vobenzyme (2–3 pills/ 3 times/day) was applied. The number of complications was 23.2 % in the control group. The adhesive bowel obstruction was noted in 6.6% of patients, bleeding and jaundice in 3.3%, the residual cavity suppuration in 10%. Complications were registered in the main group in 6.6% of children (the adhesive bowel obstruction in 3.3%, preservation of the residual cavity after a year in 3.3%). The number of relapses in the control group was 6 (12%), there were no relapses in the main group. Thus the procedure of preoperative and postoperative chemotherapy allowed avoidance of the development of relapses of hydatid disease of the liver. Omentoplasty is the most rational method of treatment of residual cavity in surgery of hydatid disease of the liver in children.